2020
DOI: 10.1021/acsnano.0c03602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Chemistry of Two-Dimensional Transition Metal Carbides and Carbonitrides (MXenes) with Gas Analysis

Abstract: MXenes, a large family of two-dimensional materials that are intensely investigated for a broad range of applications, are unstable in water, spontaneously forming TiO 2 . Several hypotheses have been proposed recently to explain the transformations of MXenes in aqueous environments based on characterization of solid products and measurements of solution pH. However, no studies of the gaseous products of these reactions have been reported. In this work, we demonstrate the use of Raman spectroscopy and gas chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 31 publications
(54 reference statements)
2
86
0
Order By: Relevance
“…While both MAX phases have comparable Ti L‐edge profiles, it can be clearly observed that the Ti L‐edge energy of Ti 2 C 0.5 N 0.5 T x MXene moves slightly to a higher energy side compared with that of Ti 2 CT x MXene, indicating a higher average for Ti oxidation state in Ti 2 C 0.5 N 0.5 T x MXene than that of Ti 2 CT x MXene. This is consistent with the reported theoretical results showing a lower stability of carbonitrides relative to their carbide counterparts 42,43 . In addition, the bonding of TiO 2− x F x and CNTiF x are located at higher binding energy regions because of the highly electronegative from F atom 61 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While both MAX phases have comparable Ti L‐edge profiles, it can be clearly observed that the Ti L‐edge energy of Ti 2 C 0.5 N 0.5 T x MXene moves slightly to a higher energy side compared with that of Ti 2 CT x MXene, indicating a higher average for Ti oxidation state in Ti 2 C 0.5 N 0.5 T x MXene than that of Ti 2 CT x MXene. This is consistent with the reported theoretical results showing a lower stability of carbonitrides relative to their carbide counterparts 42,43 . In addition, the bonding of TiO 2− x F x and CNTiF x are located at higher binding energy regions because of the highly electronegative from F atom 61 .…”
Section: Resultssupporting
confidence: 92%
“…To date, over 40 different MXene compositions have been reported; the vast majority of these MXenes are carbides with only a few exceptions—several nitrides and only one carbonitride ( viz ., Ti 3 CNT x ) 27 . The latter has shown distinct properties and behavior compared with Ti 3 C 2 T x in many applications including energy storage, 28–33 optics, 34,35 catalysis, 36–39 electromagnetic shielding, 40,41 sensing, 42,43 and so forth. This distinct behavior of Ti 3 CNT x compared with Ti 3 C 2 T x provides a strong motivation to develop other new carbonitrides to join the MXene family.…”
Section: Introductionmentioning
confidence: 99%
“…[69] The results of these weak X-X interactions in the MXenes' structure have been observed experimentally in the preferential evolution of methane gas during MXenes' hydrolysis. [73] The metallic bonding between the transition metals occurs via d-orbitals, which are not shared with carbon or nitrogen. [68] However, this metallic bonding between M-M contributes less to the lattice bond energy than M-X bonds.…”
Section: Mechanical Behavior Of Mxenesmentioning
confidence: 99%
“…However, the non-proportional relationship between the decreased pH value and increased atomic percentage of Ti(IV) does not prove this hypothesis [42]. Huang and co-worker later claimed that only CH 4 is released during degradation of carbide MXenes, whereas carbonitride MXene (Ti 3 CNT x ) released NH 3 as well [53]. After considering the oxidation mechanism, we summarize possible ways to minimize or delay the oxidation degradation of MXenes under different controlled conditions.…”
Section: Oxidative Degradation Of Mxenes and Influencing Parametersmentioning
confidence: 99%